Hubungan Kadar Ferritin dengan Indeks Eritrosit Pada Penderita Anemia Defisiensi Besi Di Laboratorium Bio Medika Gandaria Tahun 2024 - Susanti, Ellis; Latifah, Imas; Nurhidayat, Diki (Universitas Mohammad Husni Thamrin, 2024)
Anemia is a health problem with a high prevalence in Indonesia. Iron deficiency anemia, where a person's hemoglobin concentration is less than 95% of the mean value. Ferritin and MCV are sensitive parameters for iron deficiency anemia. This study aims to determine the relationship between Ferritin and MCV levels in patients with iron deficiency anemia. This research method is descriptive using secondary data at Bio Medika Gandaria Laboratory from January to June 2024 in 40 patients with Iron Deficiency Anemia (ADB). ADB patients are patients based on doctor's diagnosis on the patient's examination form. This study shows that the prevalence of Iron Deficiency Anemia patients of Female gender is higher as many as 32 patients (80%) with an average Ferritin level of 14.83 ng/mL with details of Low Ferritin levels as many as 21 patients (52.5%), Normal Ferritin 11 patients (27.5%), High Ferritin 0 patients (0.0%), and average MCV levels worth 71.70 fL with details of patients having Low MCV levels as many as 23 patients (57.5%), Normal MCV 9 patients (22.5%), High MCV 0 patients (0.0%). The results of the relationship test research using Pearson correlation, with a relationship coefficient value of p = 0.020, (p < 0.05), it can be concluded that there is a unidirectional relationship between Ferritin and MCV, the lower the Ferritin level, the lower the MCV level. Keywords: Anemia, Iron Deficiency Anemia, Ferritin, MCV